2022
DOI: 10.3390/cancers14153619
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Sorafenib, an Immune Checkpoint Inhibitor, TACE and Stereotactic Body Radiation Therapy versus Sorafenib and TACE in Advanced Hepatocellular Carcinoma Accompanied by Portal Vein Tumor Thrombus

Abstract: Background: This study compared the effectiveness of the combined administration of sorafenib, an immune checkpoint inhibitor, transcatheter arterial chemoembolization (TACE), and stereotactic body radiation therapy (SBRT) (SITS group) vs. sorafenib combined with TACE (ST group) in treating and downstaging advanced hepatocellular carcinoma (HCC) with portal vein tumor thrombus (PVTT). Methods: The present study included patients with advanced HCC and PVTT treated with one of the above combination therapies. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Three nonrandom comparative studies [18,19,21] have reported the ORR and DCR. The pooled ORR and pooled DCR were HR = 1.519 (95% CI: 1.052–2.194, P = .026) and HR = 1.194 (95% CI: 1.074–1.327), respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three nonrandom comparative studies [18,19,21] have reported the ORR and DCR. The pooled ORR and pooled DCR were HR = 1.519 (95% CI: 1.052–2.194, P = .026) and HR = 1.194 (95% CI: 1.074–1.327), respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…AEs were reported in all the included studies. Three studies [20][21][22] reported any-grade AEs and 8 studies [13][14][15][16][17][18]20,21] reported grade 3 to 4 AEs. The pooled rate of any-grade AEs was 86% (95% CI: 77-93%, P = .00).…”
Section: Aesmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the combination therapy comprising lenvatinib, TACE, PD-1 inhibitor, and I 125 seed brachytherapy is expected to have a better therapeutic effect in the treatment of HCC, especially in patients with PVTT. Two preclinical studies supported the quadruple therapy, for example, Huang Y et al 18 demonstrated that combination therapy of TACE, stereotactic Body Radiation Therapy (SBRT), sorafenib, and camrelizumab had a survival bene t, extending the PFS to 15.7 months for HCC patients with PVTT; Zhang et al 45 reported that the combination of sorafenib, an immune checkpoint inhibitor, TACE, and SBRT have a median OS of 24.2 months and PFS of 24.2 months 45 . However, our study reported a lower OS of 21.0 months and a PFS of 13.0 months.…”
Section: Discussionmentioning
confidence: 99%